2021
DOI: 10.3390/cancers13102291
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocifen Loaded Lipid Nanocapsules: A Promising Anticancer Medication against Multidrug Resistant Tumors

Abstract: Resistance of cancer cells to current chemotherapeutic drugs has obliged the scientific community to seek innovative compounds. Ferrocifens, lipophilic organometallic compounds composed of a tamoxifen scaffold covalently bound to a ferrocene moiety, have shown very interesting antiproliferative, cytotoxic and immunologic effects. The formation of ferrocenyl quinone methide plays a crucial role in the multifaceted activity of ferrocifens. Lipid nanocapsules (LNCs), meanwhile, are nanoparticles obtained by a fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 124 publications
0
12
0
Order By: Relevance
“…To achieve promising preclinical results and evaluate the effectiveness of potential therapeutic miRNAs, selecting orthotopic tumor models that create a disease-relevant environment and using cells or tissues from patients with UM (also known as patient-derived xenografts, or PDX), are important. Performing experiments on PDX models that reflect the heterogeneity and diversity of clinical tumors may decrease the dissimilarities between human tumors and preclinical models [130]. Notably, primary UM spheroids retain the histological and genetic characteristics of the primary tumor, and the use of 3D spheroids has enabled early phase drug screening [139].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve promising preclinical results and evaluate the effectiveness of potential therapeutic miRNAs, selecting orthotopic tumor models that create a disease-relevant environment and using cells or tissues from patients with UM (also known as patient-derived xenografts, or PDX), are important. Performing experiments on PDX models that reflect the heterogeneity and diversity of clinical tumors may decrease the dissimilarities between human tumors and preclinical models [130]. Notably, primary UM spheroids retain the histological and genetic characteristics of the primary tumor, and the use of 3D spheroids has enabled early phase drug screening [139].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, NP surface modifications can improve delivery efficacy and biodistribution. For instance, studies have shown that the PEG-based (DSPE-PEG2000) coating in NPs avoids clearance and improves stability in the blood [129][130][131][132]. Moreover, conjugating the surfaces of NPs with a specific ligand can significantly increase the quantity of drug delivered to the location of interest, thereby avoiding normal tissues, enhancing the therapeutic efficiency and limiting the adverse effects of the drugs [77,130].…”
Section: Modification Of Np Surfaces For Improving Biocompatibility and Active Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, some members of the family exhibit strong anti-proliferative effects, both in vitro and in vivo, associated with a cytotoxic activity while hydroxy tamoxifen shows only an anti-hormonal effect (Allard et al, 2008;Jaouen et al, 2015;Lainé et al, 2014). This is for example the case for P722 (54, Chart 9) which has been identified so far as the most cytotoxic member of the family, on MDA-MB231, triple negative breast cancer cells (IC50 = 35 nM) and to be highly cytotoxic also on several MDR cell lines (Idlas et al, 2021;Wang et al, 2019). ROS production observed with ferrocifens (Jaouen et al, 2015) make them potential candidates as agent capable of inducing ICD (Terenzi et al, 2016).…”
Section: Immunogenic Cell Death Strategymentioning
confidence: 94%
“…These molecules are lipophilic thus they can be in vivo administered only after formulation. It has been shown by Passirani and her group that lipid nanocapsules are a very well-suited formulation for this family of molecules (Idlas et al, 2021). These nanoparticles present a hybrid structure between polymer NPs and liposomes and are prepared by a solvent-free process.…”
Section: Nps and Molecules Associated With Immunogenic Cell Death (Icd)mentioning
confidence: 99%